Effect of magnetic field and non-uniform temperature gradient on Marangoni convection with free-slip bottom - Mohamed Isa, Siti Suziliana Putri; Md. Arifin, Norihan; Nazar, Roslinda; Saad, Mohd Noor (Research India Publications, 2010)
The effect of magnetic field on the onset of Marangoni convection in a horizontal layer with a free-slip bottom heated from below and cooled from above with non-uniform basic temperature gradient is considered. A linear stability analysis is performed to undertake a detailed investigation. The eigenvalues are obtained for lower rigid isothermal and upper free adiabatic boundaries. The influence of various parameters on the onset of convection has been analyzed. Six non-uniform basic temperature profiles are considered and some general conclusions about their destabilizing effects are presented.